Chloride Reduction Therapy with Furosemide: Short-Term Effects in Children with Acute Respiratory Failure - Nozawa, Hisataka; Tsuboi, Norihiko; Oi, Tadashi; Takezawa, Yoshiki; Osawa, Ichiro; Nishimura, Nao; Nakagawa, Satoshi (Journal of Pediatric Intensive Care, 2021)
From the perspective of the Stewart approach, it is known that expansion of the sodium chloride ion difference (SCD) induces alkalosis. We investigated the role of SCD expansion by furosemide-induced chloride reduction in pediatric patients with acute respiratory failure. We included patients admitted to our pediatric intensive care unit intubated for acute respiratory failure without underlying diseases, and excluded patients receiving extracorporeal circulation therapy (extracorporeal membrane oxygenation and/or renal replacement therapy). We classified eligible patients into the following two groups: case—those intubated who received furosemide within 24 hours, and control—those intubated who did not receive furosemide within 48 hours. Primary outcomes included SCD, partial pressure of carbon dioxide (PaCO2), and pH results from arterial blood gas samples obtained over 48 hours following intubation. Multiple regression analysis was also performed to evaluate the effects of SCD and PaCO2 changes on pH. Twenty-six patients were included of which 13 patients were assigned to each of the two groups. A total of 215 gas samples were analyzed. SCD (median [mEq/L] [interquartile range]) 48 hours after intubation significantly increased in the case group compared with the control group (37 [33–38] vs. 31 [30–34]; p = 0.005). Although hypercapnia persisted in the case group, the pH (median [interquartile range]) remained unchanged in both groups (7.454 [7.420–7.467] vs. 7.425 [7.421–7.436]; p = 0.089). SCD and PaCO2 were independently associated with pH (p < 0.001 for each regression coefficient). As a result, we provide evidence that SCD expansion with furosemide may be useful in maintaining pH within the normal range in pediatric patients with acute respiratory failure complicated by concurrent metabolic acidosis.
Keywords: acid–base equilibrium; mechanical ventilation; chloride; furosemide